Origin of Circulating Free DNA in Sepsis: Analysis of the CLP Mouse Model - Shigeto Hamaguchi; Yukihiro Akeda; Norihisa Yamamoto; Masafumi Seki; Kouji Yamamoto; Kazunori Oishi; Kazunori Tomono (Mediators of Inflammation)
Recently, it has been reported that circulating free DNA (cf-DNA) in the blood is increased in various infectious diseases, including sepsis. Moreover, a relationship between cf-DNA and neutrophil extracellular traps (NETs) has been suggested. However, it is still unclear what the source and physiological role of cf-DNA in sepsis are. In this study, we examined the source of cf-DNA by detecting citrullinated histone H3, a characteristic feature of NET formation, in cecal ligation and puncture- (CLP-)operated mice. In addition, neutrophil depletion using anti-Ly6G antibodies was performed to assess the association between neutrophils and cf-DNA. Increased cf-DNA levels were observed only in CLP mice and not in the control groups; the qPCR findings revealed that the cf-DNA was mainly host-derived, even in bacteremic conditions. Citrullinated histone H3 was not increased in the neutrophils upon CLP, and the depletion of neutrophils showed limited effects on decreasing the amount of cf-DNA. Taken together, these results suggested that elevated cf-DNA levels during early-phase sepsis may represent a candidate biomarker for the severity of sepsis and that, contrary to previous findings, cf-DNA is not derived from neutrophils or NETs.